2020
DOI: 10.1186/s40902-020-00256-5
|View full text |Cite
|
Sign up to set email alerts
|

Being a front-line dentist during the Covid-19 pandemic: a literature review

Abstract: Coronavirus is an enveloped virus with positive-sense single-stranded RNA. Coronavirus infection in humans mainly affects the upper respiratory tract and to a lesser extent the gastrointestinal tract. Clinical symptoms of coronavirus infections can range from relatively mild (similar to the common cold) to severe (bronchitis, pneumonia, and renal involvement). The disease caused by the 2019 novel coronavirus (2019-nCoV) was called Covid-19 by the World Health Organization in February 2020. Face-to-face communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
199
1
43

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(244 citation statements)
references
References 49 publications
1
199
1
43
Order By: Relevance
“…Dentists, who are an essential part of the health professional group, are front liners in this pandemic. Moreover, areas of professional expertise of dentist are oral cavity and teeth put them in the most vulnerable position for being infected by COVID-19 Ataş and Yildirim 2020;Fallahi et al 2020;Khader et al 2020). Therefore, a dentist should have proper knowledge and practice according to standard guidelines to prevent the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentists, who are an essential part of the health professional group, are front liners in this pandemic. Moreover, areas of professional expertise of dentist are oral cavity and teeth put them in the most vulnerable position for being infected by COVID-19 Ataş and Yildirim 2020;Fallahi et al 2020;Khader et al 2020). Therefore, a dentist should have proper knowledge and practice according to standard guidelines to prevent the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study data suggested that SARS-CoV-2 virus might remain viable and infectious in aerosols and droplets for hours, which poses more signi cant threats for dentists to be infected and subsequently spread to their colleagues, families and other patients (Van Doremalen et al 2020;. Dentists may also get infected from unrecognized and under surveillance COVID-19 individuals; thus, contamination may occur before the symptoms appear (Ataş and Yildirim 2020) and indirect contact with contaminated surfaces and instruments (Fallahi et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Even though Italian dental offices have never stopped working, they limited their practice ensuring just urgent and emergency dental care treatments. Droplet production and blood and saliva exposure put dental practitioners at high risk of contagion during their routine procedures [ 9 , 10 , 11 ]. Aerosol or droplets inhalation from SARS-CoV-2 positive individuals and even the direct contact with mucous membranes, oral fluids and contaminated instruments and surfaces could enhance virus transmission during dental procedures [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nature and extent of changes depend on the amount of risk for disease transmission involved in a work set-up [ 24 ]. HCWs have always been in the forefront battling the pandemic, and thus also remained at the high risk for acquiring and transmitting disease [ 12 , 25 , 26 ]. Institutions involved in any form of health care delivery (academic, clinical care or both) required to maintain high standard of infection control protocol [ 27 ].…”
Section: Dental Radiology and Covid-19mentioning
confidence: 99%